GENETIC DIVERGENCE STUDIES IN BLACKGRAM (Vigna mungo L.) FOR YIELD AND QUANTITATIVE TRAITS - K. SARAVANAN, S. SRI VIDYA, T. SABESAN (Journal of Phytology, 2018)
The genetic divergence was estimated in 21 blackgram genotypes, using Mahalanobis D2 statistics. The experiment was conducted at Plant Breeding Farm, Department of Genetics and Plant Breeding, Faculty of Agriculture, Annamalai University during January 2017. Analysis of genetic variance indicated the presence of sufficient variation among the selected genotypes. Based on 11 morphological and quality characters namely, days to first flower, plant height (cm), number of primary branches, number of clusters per plant, number of pods per plant, pod length (cm), pod weight (g), number of seeds per pod, seed size (cm), 100 seed weight (g), yield per plant (g), these genotypes were grouped into 5 clusters showing fair degree of relationship between geographical distribution and genetic divergence. Cluster I, with 6 genotypes, was the largest cluster followed by cluster IV and V with 5 genotypes. The intra cluster distance was maximum (D=809.83) in cluster V. The maximum inter cluster distance (D2=2932.162) was recorded between cluster II and III. All cluster mean values are distributed in relatively distant clusters. Traits like yield per plant (70.47%) followed by 100 seed weight (17%) were the major contributors to total genetic divergence.